2021
DOI: 10.1021/acsanm.1c01453
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electrical Properties of Cellulose Nanocrystals through Laser-Induced Graphitization for UV Photodetectors

Abstract: Laser-induced graphene from abundant and renewable biobased carbon sources may open the way for sustainable and lowcost electronic device generation. Yet little progress has been made on nanocellulose-based materials to produce laser-induced graphene (LIG). In this work, we demonstrate the versatility of the laserassisted technique to promote graphitization of pineapple cellulose nanocrystals (CNCs), aimed at UV photodetectors. CNCs tablets are used as carbon-based precursors to photonically synthesize LIG nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…When fabricating a UVC photodetector, it is necessary to consider whether a low-temperature and simple process is possible. This is because it is essential to develop sustainable electronic devices to reduce the impacts on the environment of energy consumption and waste [ 15 , 16 ]. Low energy processes make it possible to produce more eco-friendly devices [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…When fabricating a UVC photodetector, it is necessary to consider whether a low-temperature and simple process is possible. This is because it is essential to develop sustainable electronic devices to reduce the impacts on the environment of energy consumption and waste [ 15 , 16 ]. Low energy processes make it possible to produce more eco-friendly devices [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…32 The electrical performance of LIG can be tuned by changing laser parameters. 33 LIG has been applied for electronic devices including supercapacitors 34 and motion sensors. 31,32,35 In 2019, Stanford et al applied laser-induced graphitization for the fabrication of electrodes of TENGs for the first time.…”
Section: ■ Introductionmentioning
confidence: 99%
“…After the revival of the method by demonstrating the formation of graphene on polyimide (PI) in 2014, it has been reported that LIG can also be formed on low-cost materials such as paper and cork . The electrical performance of LIG can be tuned by changing laser parameters . LIG has been applied for electronic devices including supercapacitors and motion sensors. ,, In 2019, Stanford et al applied laser-induced graphitization for the fabrication of electrodes of TENGs for the first time .…”
Section: Introductionmentioning
confidence: 99%
“…Screen printing was used to print nanopaper composite gated transistors (NCGTs), avoiding expensive conventional microfabrication techniques, such as sputtering and evaporation, which are commonly used in fabricating paper-gated transistors. [11,13,34] Inspired by the recent developments done in our research group in the field of printed oxide-based electronics on paper, [35][36][37] a screen-printable water-based ink composed of zinc oxide nanostructures was used to pattern the semiconductor layer of the transistors directly on the ACICC membrane. The adoption of planar configuration to further simplify the design of the transistors enables the fabrication of the first fully printed oxide-based NCGTs and integrated "universal" logic gates (NAND and NOR) with low-voltage operation, capable of withstanding extreme mechanical deformation under outward folding.…”
Section: Introductionmentioning
confidence: 99%